Ultrasound compared with clinical examination in infantile hypertrophic pyloric stenosis. Issue 4 (October 1996) - Godbole, P; Sprigg, A; Dickson, J A; Lin, P C
Abstract : OBJECTIVES: To assess the accuracy of clinical examination as compared with ultrasound imaging in the diagnosis of infantile hypertrophic pyloric stenosis. Duration of hospital stay, time between admission and surgery, and financial implications were also considered. DESIGN: A prospective study of patients referred to the surgical team with a possible diagnosis of pyloric stenosis from May 1993 to January 1995. SETTING: Neonatal and paediatric surgical wards and imaging department of a paediatric teaching hospital. SUBJECTS: 116 patients referred to the surgical team with a possible diagnosis of pyloric stenosis. RESULTS: 75 patients in this study had pyloric stenosis (64.6%). Clinical examination had a sensitivity of 72%, specificity of 97%, with a positive and negative predictive value of 98% and 61% respectively. There were 16 diagnostic errors (one false positive and 15 false negative). Ultrasound imaging had a sensitivity of 97%, specificity of 100%, with a positive and negative predictive value of 100% and 98% respectively. There was one diagnostic error (one false negative). Eight patients required repeat scans for confirmation of the diagnosis. On review of the initial scans in these patients, seven were noted to have inaccurate measurements due to poor technique. The average time between repeated scans was 28.2 hours. Ultrasound imaging cost 13.90 pounds per scan and initiated a change in management only in the clinically false negative group at a cost of 52 pounds per patient. The average duration of hospital stay was 3.1 days and the mean time between admission and surgery was 19.2 hours. The total cost for treatment of a patient with pyloric stenosis was 1602 pounds. CONCLUSION: Ultrasound imaging should be reserved for those cases where clinical examination is negative and should be carried out by sonographers who see enough cases to maintain their expertise.